Q: Factor the polynomial x3 - 3x2 plus x - 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

Answer this ques Which polynomial represents the sum below?(-x3 + 3x2 + 3) + (3x2 + x + 4)tionâ€¦

x3 + 3x2 - 6x - 8 = (x - 2)(x2 + 5x + 4) = (x - 2)(x + 1)(x + 4)

y2=x3+3x2

If you mean "factors", the two monomials have the common factor x2. Divide each factor by x2 to get the other factor.

x3 + 3x2 - 4x -12 x2(x + 3) - 4(x + 3) (x2 - 4)(x+3)

Related questions

(x2 + 1)(x - 3)

x3 - 3x2 + x - 3 = (x - 3)(x2 + 1)

x(x + 2)(x - 5)

Answer this ques Which polynomial represents the sum below?(-x3 + 3x2 + 3) + (3x2 + x + 4)tionâ€¦

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)

x3 + 3x2 - 6x - 8 = (x - 2)(x2 + 5x + 4) = (x - 2)(x + 1)(x + 4)

x3 - 2x2 + x - 2 =(x - 2)(x2 + 1)

y2=x3+3x2

x3 + 3x2 - 9x + 5 = 0 has roots of -5,1 and 1. CHECK : x3 + 3x2 - 9x + 5 = (x + 5)(x - 1)(x - 1)

If you mean "factors", the two monomials have the common factor x2. Divide each factor by x2 to get the other factor.

x3 + 3x2 - 4x -12 x2(x + 3) - 4(x + 3) (x2 - 4)(x+3)

True.